Um estudo sobre as relações sintático-semânticas do verbo passar para identificação de verbo-suporte - Dantas, Juliene do Nascimento (2011)
In this paper we study the structures made by the verb + NS Skip to identify its use as a support verb. 90 structures are observed in order to develop a descriptive study of the types of structures formed with the verb Skip SN + (noun phrase), taking into account the distributional properties that are related to the nature of their complements, in view of the wide occurrence of these formations in space and its use of language in order to identify the structures that behave like verb-support. For this, we use some principles of the grammar of valences, the functionalist studies, studies of the lexicon and the identification criteria proposed by the lexicon-grammar.